The Effect of Color and Positional Noise on Reading Performance in Human Vision - Abdullah Alsalhi; Northway, Nadia; Walsh, Glyn; Elmadina, Abd Elaziz Mohamed (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Reading can be described as a complex cognitive process of decrypting signs to create meaning. Eventually, it is a way of language achievement, communication, and sharing information and ideas. Changing lighting and color are known to improve visual comfort and the perceptual difficulties that affect reading for those with poor vision. AIM: This study aims to investigate the effect of changing the wavelengths and different levels of positional noise on reading performance for participants with best-corrected distant visual acuity (BCVA) of 6/6 or better. METHODOLOGY: Twenty English speakers with BCVA 6/6 or better were asked to read words presented in a printed format. The stimuli were black print words in a horizontal arrangement on matte white card. They were degraded using positional noise produced by random vertical displacements of the letter position below or above the horizontal line on three levels. RESULTS: Introducing positional noise affected word recognition differently with different wavelengths. The role of short wavelength in enhancing orthographic reading and word recognition is clear – they reduce the effects of positional noise. The error rate and duration time have different effects with different wavelengths, even when positional noise is introduced. CONCLUSION: The reading rate is not affected by changing the wavelength of the light. However, the mean differences in wpm were affected by changing the wavelengths. Also, introducing positional noise affects word recognition differently with different wavelengths.